Metal-doped three-dimensional covalent organic framework material, preparation method thereof, negative electrode with metal-doped three-dimensional covalent organic framework material and secondary battery with metal-doped three-dimensional covalent organic framework material
By connecting 9,10-dihydro-9,10-[1,2] benzoanthracene with the doped third transition system metal cerium, iridium, platinum, and gold to form a metal doped three-dimensional covalent organic frame material, the problem of insufficient charge blocking and catalytic activity in the prior art is solved, and efficient electrochemical catalysis and performance improvement of lithium metal batteries is achieved.
Patent Information
- Application Number
- CN202411453279.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The lack of research on the three-dimensional covalent organic frame materials formed by connecting porphyrin molecules doped with cerium, iridium, platinum, and gold to 9,10-dihydro-9,10-[1,2]benzoanthracene, its electrode performance and battery performance in the prior art, resulting in the problems of charge blocking and insufficient catalytic activity in electrochemical systems.
By connecting 9,10-dihydro-9,10-[1,2]benzoanthracene with the doped third transition metals cerium, iridium, platinum, and gold, the β-tetrasubstituted porphyrin is directly connected through nitrogen atoms to form a metal-doped three-dimensional covalent organic frame material. The unique advantages of these metals' 4f orbitals are utilized to enhance the conductivity and catalytic activity of the material.
It has achieved shortening the mass transfer path, reducing charge blockage, improving the conductivity and catalytic activity of the material, accelerating proton conduction, and strengthening the kinetics of mass transfer reactions, providing an efficient catalytic platform for electrochemical reactions, and significantly improving the cycling performance and safety of lithium metal batteries.
Smart Images

Figure CN119552329A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemical functional composite materials, in particular to a metal-doped three-dimensional covalent organic framework material, a preparation method thereof, a negative electrode having the material, and a secondary battery having the negative electrode. Background Art
[0002] Covalent organic framework (COFs) materials are a class of porous framework compounds formed by organic small molecule skeleton molecules connected by strong covalent bonds. In recent years, covalent organic framework materials (COFs) have gradually become a research hotspot for new battery materials due to their advantages such as designable pore parameters, strong thermochemical stability, and designable regional electron enrichment properties. With the in-depth study of three-dimensional skeleton molecules, a research branch of three-dimensional COFs materials has emerged. Compared with two-dimensional COFs materials, three-dimensional COFs materials can establish a unique three-dimensional pore structure, which brings higher mass transfer efficiency and more catalytic sites to the heterogeneous catalytic process, and has an optimistic research prospect.
[0003] However, there is relatively little research on three-dimensional COFs materials. There is no research on the three-dimensional COFs materials formed by connecting cerium, iridium, platinum, and gold-doped porphyrin molecules with 9,10-dihydro-9,10-[1,2]benzanthracene and their electrode properties and battery performance. Summary of the invention
[0004] Based on this, the purpose of the present invention is to provide a metal-doped three-dimensional covalent organic framework material, so that 9,10-dihydro-9,10-[1,2]benzanthracene and β-tetrasubstituted porphyrin doped with third transition metal cerium, iridium, platinum and gold are directly connected through nitrogen atoms to form a three-dimensional covalent organic framework material, which not only shortens the mass transfer path between the two molecules and reduces charge blockage, but also makes full use of the unique advantages of 4f orbitals and 5d orbitals of cerium, iridium, platinum and gold, improves the conductivity and catalytic activity of the material, accelerates proton conduction, strengthens mass transfer reaction kinetics, and provides an efficient catalytic platform for electrochemical reactions.
[0005] The three-dimensional COF material of the present invention constructs a porous network structure that not only provides a stable mass transfer path, but also effectively promotes multi-scale ion transport through its point-line transport mechanism. This orderly pore design makes the transmission of protons, lithium ions, etc. in the electrochemical system more efficient, reduces charge blockage, and enhances the kinetic performance of the overall mass transfer reaction.
[0006] The present invention uses β-tetra-R-based porphyrin and 9,10-dihydro-9,10-[1,2]benzanthracene doped with metal cerium (Ce), iridium (Ir), platinum (Pt) or gold (Au) as monomers to synthesize a covalent organic framework (COF) with significant advantages, especially in terms of mass transfer coupling and proton hybridization. Ce, Ir, Pt, and Au are doped into the β-tetra-R-based porphyrin skeleton to form a COF material, which can further enhance the conductivity and electrochemical activity of the COF material. These metal-doped COF materials are modified on the lithium metal negative electrode, which can not only evenly distribute lithium ion deposition, but also effectively inhibit the growth of lithium dendrites, thereby improving the cycle performance and safety of lithium metal batteries. Under the action of 5d and 4f orbitals, metals such as Ce, Ir, Pt, and Au not only have significant advantages in proton-coupled electron transfer reactions, but also have outstanding performance in catalytic kinetics. Doping Ce, Ir, Pt, and Au into the β-tetra-R-based porphyrin skeleton to form a COF material can not only effectively improve the conductivity and catalytic activity of the material, but also significantly accelerate proton conduction and enhance the mass transfer reaction kinetics. Specifically, the 4f orbital of cerium (Ce) has a highly localized electronic structure and exhibits significant electron transfer ability during proton coupling. 3+ and Ce 4+ The redox cycle of gold provides a stable charge transfer channel, further improving the proton transfer and coupling efficiency. The partially filled 5d orbital of iridium exhibits excellent catalytic performance in the proton hybridization process, strengthening charge transfer and proton coupling. The half-filled 5d orbital of platinum can provide a stable and efficient proton transfer path, which is suitable for kinetic acceleration in mass transfer reactions. The empty 5d orbital of gold makes it highly stable in proton coupling reactions, especially in a high electrochemical stability environment, showing outstanding catalytic performance.
[0007] The technical solution of the present invention is achieved by the following methods:
[0008] A metal-doped three-dimensional covalent organic framework material is formed by connecting a 9,10-dihydro-9,10-[1,2]benzanthracene skeleton and a metal-doped β-tetra-R-based porphyrin skeleton through nitrogen atoms. The 9,10-dihydro-9,10-[1,2]benzanthracene skeleton comprises two first-dimensional connection sites, two second-dimensional connection sites and two third-dimensional connection sites. For any of the 9,10-dihydro-9,10-[1,2]benzanthracene skeletons, at least one of the first-dimensional connection sites is connected to the nitrogen atom through a double bond, at least one of the second-dimensional connection sites is connected to the nitrogen atom through a double bond, and at least one of the third-dimensional connection sites is connected to the nitrogen atom through a double bond. Four R groups of the metal-doped β-tetra-R-based porphyrin skeleton are respectively connected to one of the nitrogen atoms through a single bond. The metal comprises one of cerium, iridium, platinum and gold.
[0009] The metal-doped three-dimensional covalent organic framework material of the present invention forms a three-dimensional covalent organic framework material by directly connecting 9,10-dihydro-9,10-[1,2]benzanthracene and β-tetrasubstituted porphyrin doped with third transition metal cerium, iridium, platinum and gold through nitrogen atoms, which not only shortens the mass transfer path between the two molecules and reduces charge blockage, but also makes full use of the unique advantages of 4f orbitals and 5d orbitals peculiar to cerium, iridium, platinum and gold, improves the conductivity and catalytic activity of the material, accelerates proton conduction, strengthens mass transfer reaction kinetics, and provides an efficient catalytic platform for electrochemical reactions.
[0010] Furthermore, the structural formula of the metal-doped three-dimensional covalent organic framework material is:
[0011]
[0012] Wherein, M is one of cerium, iridium, platinum and gold. The R group is selected from phenyl, which further strengthens the metal-doped β-tetra-R-based porphyrin skeleton with a π-conjugated system, improves the electron transfer rate, and improves the conductivity and ion conductivity of the obtained three-dimensional covalent organic framework material; the six connection sites of the 9,10-dihydro-9,10-[1,2]benzanthracene skeleton are all connected to the porphyrin skeleton, increasing the molecular distribution density of the covalent organic framework material, improving the mass transfer efficiency, and bringing more catalytic sites.
[0013] The present invention also provides a method for preparing any of the above-mentioned metal-doped three-dimensional covalent organic framework materials, comprising the following steps: uniformly mixing metal-doped 5,10,15,20-tetrakis(4-aminophenyl)porphyrin with a three-dimensional keto compound, a glacial acetic acid solution and a first solvent, degassing, reacting at 100-150° C. for 72-120 hours, filtering, washing and drying to obtain the metal-doped three-dimensional covalent organic framework material;
[0014] The metal is one of cerium, iridium, platinum and gold; the three-dimensional keto compound is formed by connecting the 9,10-dihydro-9,10-[1,2]benzanthracene skeleton and at least three oxygen atoms through double bonds, wherein at least one of the first-dimensional connection sites is connected to the oxygen atom, at least one of the second-dimensional connection sites is connected to the oxygen atom, and at least one of the third-dimensional connection sites is connected to the oxygen atom; the first solvent includes one or more of methanol, pyridine, N-methylpyrrolidone, o-dichlorobenzene, n-butanol, mesitylene and 1,4-dioxane.
[0015] Furthermore, the three-dimensional keto compound is 9,10-[1,2]benzanthracene-2,3,6,7,14,15(9H,10H)-hexanone.
[0016] Furthermore, the molar ratio of the keto carbonyl group in the three-dimensional keto compound to the amino group in the metal-doped 5,10,15,20-tetrakis(4-aminophenyl)porphyrin is 1:(1-1.2).
[0017] Furthermore, the sum of the masses of the three-dimensional keto compound and the metal-doped 5,10,15,20-tetrakis(4-aminophenyl)porphyrin: the volume of the first solvent = 20 mg:(1-2) ml, the volume ratio of the first solvent to the glacial acetic acid solution is 1:(0.1-0.2), and the concentration of the glacial acetic acid solution is 6-12 mol / L.
[0018] The present invention also provides a negative electrode, comprising an active metal and any of the above-mentioned metal-doped three-dimensional covalent organic framework materials, wherein the active metal comprises one or more of lithium, sodium, potassium and zinc.
[0019] Furthermore, the preparation method of the negative electrode comprises the following steps: uniformly dispersing the metal-doped three-dimensional covalent organic framework material in a second solvent to obtain a mixed solution, uniformly drop-coating the mixed solution on the surface of the active metal, and heating the active metal until the second solvent on the surface of the active metal is completely volatilized to obtain the negative electrode;
[0020] The mass of the metal-doped three-dimensional covalent organic framework material: the volume of the second solvent = 1 mg: (1-3) mL;
[0021] The amount of the mixed solution dripped on the active metal surface is 0.17-0.28 μL / mm 2 If the dosage is less than 0.17 μL / mm 2 The contact area between the mixed solution and the active metal surface is too small, and the metal sheet is not completely covered. If the amount is greater than 0.28μL / mm 2 , the mixed solution will overflow the area on the active metal surface that needs to be dripped, resulting in waste of material.
[0022] Furthermore, the method for preparing the negative electrode further comprises the following steps: heating the active metal to a temperature of 40-80° C. and heating the active metal for a time of 4-12 hours.
[0023] The present invention also provides a secondary battery, comprising a battery housing and any one of the above-mentioned negative electrodes, a lithium iron phosphate positive electrode, a separator and an electrolyte located in the battery housing, wherein the separator is located between the positive electrode and the negative electrode.
[0024] Compared with the prior art, the technical effects of the present invention are:
[0025] (1) The present invention provides four different metal porphyrin-three-dimensional ketone monomer combinations to prepare COF materials with excellent electrochemical properties, significantly improving the cycle stability and capacity retention rate of metal lithium secondary batteries.
[0026] Specifically, 9,10-dihydro-9,10-[1,2]benzanthracene and β-tetrasubstituted porphyrin doped with third transition metals cerium, iridium, platinum and gold are directly connected through nitrogen atoms to form a three-dimensional covalent organic framework material. This not only shortens the mass transfer path between the two molecules and reduces charge blockage, but also makes full use of the unique advantages of the 4f orbitals and 5d orbitals of cerium, iridium, platinum and gold to improve the conductivity and catalytic activity of the material, accelerate proton conduction, enhance mass transfer reaction kinetics, and provide an efficient catalytic platform for electrochemical reactions. By adjusting the electronegativity and electron cloud density of the COF skeleton, the adsorption capacity and migration efficiency of lithium ions are improved, and the growth of lithium dendrites is effectively inhibited, thereby improving the cycle life of the battery.
[0027] The COF design of the present invention utilizes the synergistic effect of ketone monomers and transition metal coordination centers, which not only optimizes the electronic structure of the COF skeleton, but also optimizes the electrolyte decomposition process, which is conducive to the formation of a uniform and dense SEI film, reduces the growth of lithium dendrites, prolongs the cycle life of the battery, and improves safety.
[0028] (2) The strong π-conjugated system contained in the β-tetrasubstituted porphyrin doped with the third transition metal cerium, iridium, platinum, and gold combines with the porous skeleton of the three-dimensional COF, which, on the one hand, significantly improves the electron transfer rate and promotes the conductivity and ion conductivity of the three-dimensional COF material; on the other hand, it regulates the formation and stability of the solid electrolyte interface (SEI) film in the lithium metal battery through its electronic structure; on the other hand, the metal center in the β-tetrasubstituted porphyrin doped with the third transition metal cerium, iridium, platinum, and gold can provide a variety of redox active sites, which help accelerate the catalytic process and improve the overall energy conversion efficiency.
[0029] (3) Using 5,10,15,20-tetrakis(4-aminophenyl)porphyrin cerium, 5,10,15,20-tetrakis(4-aminophenyl)porphyrin iridium, 5,10,15,20-tetrakis(4-aminophenyl)porphyrin platinum and 5,10,15,20-tetrakis(4-aminophenyl)porphyrin gold as the amino monomers of COF can significantly enhance the electrochemical performance, ionic conductivity, mechanical stability and thermal stability of COF materials through the unique electronic structure and redox activity of metal porphyrin. These advantages make the synthesized COF materials very suitable for application in lithium metal batteries.
[0030] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of the basic structure of a metal-doped three-dimensional covalent organic framework material according to an embodiment of the present invention;
[0032] Figure 2 This is a TEM image of a metal-doped three-dimensional covalent organic framework material according to an embodiment of the present invention;
[0033] Figure 3 A nitrogen adsorption-desorption curve of a metal-doped three-dimensional covalent organic framework material according to an embodiment of the present invention;
[0034] Figure 4 A pore size distribution diagram of a metal-doped three-dimensional covalent organic framework material according to an embodiment of the present invention;
[0035] Figure 5 This is a schematic diagram of the basic structure of the metal-doped three-dimensional covalent organic framework material described in a first ratio of the present invention. DETAILED DESCRIPTION
[0036] It should be clear that the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the embodiments of the present application.
[0037] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the embodiments of the present application. The singular forms of "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0038] When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. On the contrary, they are merely examples of devices and methods consistent with some aspects of the present application as detailed in the attached claims. In the description of the present application, it should be understood that the terms "first", "second", "third", etc. are only used to distinguish similar objects, and do not have to be used to describe a specific order or sequence, nor can they be understood as indicating or implying relative importance. For those of ordinary skill in the art, the specific meanings of the above terms in the present application can be understood according to the specific circumstances.
[0039] In addition, in the description of this application, unless otherwise specified, "plurality" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0040] It should be understood that the embodiments of the present application are not limited to the precise structures described above and shown in the drawings, and various modifications and changes can be made without departing from the scope thereof. The scope of the embodiments of the present application is limited only by the appended claims.
[0041] It should be noted that the 9,10-dihydro-9,10-[1,2]benzanthracene skeleton described in the present invention is composed of 9,10-dihydro-9,10-[1,2]benzanthracene and two first-dimensional connection sites, two second-dimensional connection sites and two third-dimensional connection sites. The two first-dimensional connection sites described in the present invention refer to the carbon at position 2 and the carbon at position 3 of 9,10-dihydro-9,10-[1,2]benzanthracene, the two second-dimensional connection sites described in the present invention refer to the carbon at position 6 and the carbon at position 7 of 9,10-dihydro-9,10-[1,2]benzanthracene, and the two third-dimensional connection sites described in the present invention refer to the carbon at position 14 and the carbon at position 15 of 9,10-dihydro-9,10-[1,2]benzanthracene.
[0042] It should be noted that the metal-doped β-tetra-R-porphyrin skeleton described in the present invention is formed by replacing the hydrogen atoms on the four β-carbons of porphine (corresponding to the carbons at positions 5, 10, 15 and 20 of porphine) with R groups and doping with metal M. M described in the present invention refers to any metal, and the specific metal corresponding to M in different substances / structures should be based on the examples given in the present invention.
[0043] The metal-doped three-dimensional covalent organic framework material of the present invention allows 9,10-dihydro-9,10-[1,2]benzanthracene and beta-tetrasubstituted porphyrin doped with third transition metal cerium, iridium, platinum and gold to be directly connected through nitrogen atoms to form a three-dimensional covalent organic framework material, which not only shortens the mass transfer path between the two molecules and reduces charge blockage, but also fully utilizes the unique advantages of 4f orbitals and 5d orbitals peculiar to cerium, iridium, platinum and gold, improves the conductivity and catalytic activity of the material, accelerates proton conduction, strengthens mass transfer reaction kinetics, and provides an efficient catalytic platform for electrochemical reactions.
[0044] Furthermore, the structural formula of the metal-doped three-dimensional covalent organic framework material is:
[0045]
[0046] Wherein, M is one of cerium, iridium, platinum and gold. The R group is selected from phenyl, which further strengthens the metal-doped β-tetra-R-based porphyrin skeleton with a π-conjugated system, improves the electron transfer rate, and improves the conductivity and ion conductivity of the obtained three-dimensional covalent organic framework material; the six connection sites of the 9,10-dihydro-9,10-[1,2]benzanthracene skeleton are all connected to the porphyrin skeleton, increasing the molecular distribution density of the covalent organic framework material, improving the mass transfer efficiency, and bringing more catalytic sites.
[0047] The present invention also provides a method for preparing any of the above-mentioned metal-doped three-dimensional covalent organic framework materials, comprising the following steps: uniformly mixing metal-doped 5,10,15,20-tetrakis(4-aminophenyl)porphyrin with a three-dimensional keto compound, a glacial acetic acid solution and a first solvent, degassing, reacting at 100-150° C. for 72-120 hours, filtering, washing and drying to obtain the metal-doped three-dimensional covalent organic framework material;
[0048] The metal is one of cerium, iridium, platinum and gold; the three-dimensional keto compound is formed by connecting the 9,10-dihydro-9,10-[1,2]benzanthracene skeleton and at least three oxygen atoms through double bonds, wherein at least one of the first-dimensional connection sites is connected to the oxygen atom, at least one of the second-dimensional connection sites is connected to the oxygen atom, and at least one of the third-dimensional connection sites is connected to the oxygen atom; the first solvent includes one or more of methanol, pyridine, N-methylpyrrolidone, o-dichlorobenzene, n-butanol, mesitylene and 1,4-dioxane.
[0049] Furthermore, the three-dimensional keto compound is 9,10-[1,2]benzanthracene-2,3,6,7,14,15(9H,10H)-hexanone.
[0050] Furthermore, the molar ratio of the keto carbonyl group in the three-dimensional keto compound to the amino group in the metal-doped 5,10,15,20-tetrakis(4-aminophenyl)porphyrin is 1:(1-1.2).
[0051] Furthermore, the sum of the masses of the three-dimensional keto compound and the metal-doped 5,10,15,20-tetrakis(4-aminophenyl)porphyrin: the volume of the first solvent = 20 mg:(1-2) ml, the volume ratio of the first solvent to the glacial acetic acid solution is 1:(0.1-0.2), and the concentration of the glacial acetic acid solution is 6-12 mol / L.
[0052] The present invention also provides a negative electrode, comprising an active metal and any of the above-mentioned metal-doped three-dimensional covalent organic framework materials, wherein the active metal comprises one or more of lithium, sodium, potassium and zinc.
[0053] Furthermore, the preparation method of the negative electrode comprises the following steps: uniformly dispersing the metal-doped three-dimensional covalent organic framework material in a second solvent to obtain a mixed solution, uniformly drop-coating the mixed solution on the surface of the active metal, and heating the active metal until the second solvent on the surface of the active metal is completely volatilized to obtain the negative electrode;
[0054] The mass of the metal-doped three-dimensional covalent organic framework material: the volume of the second solvent = 1 mg: (1-3) mL;
[0055] The amount of the mixed solution dripped on the active metal surface is 0.17-0.28 μL / mm 2 If the dosage is less than 0.17 μL / mm 2 The contact area between the mixed solution and the active metal surface is too small, and the metal sheet is not completely covered. If the amount is greater than 0.28μL / mm 2 , the mixed solution will overflow the area on the active metal surface that needs to be dripped, resulting in waste of material.
[0056] Furthermore, the method for preparing the negative electrode further comprises the following steps: heating the active metal to a temperature of 40-80° C. and heating the active metal for a time of 4-12 hours.
[0057] The present invention also provides a secondary battery comprising a battery housing and any one of the above-mentioned negative electrodes, a lithium iron phosphate positive electrode, a separator and an electrolyte located in the battery housing, wherein the separator is located between the positive electrode and the negative electrode.
[0058] The physical properties and test methods of the embodiments or comparative examples of the present invention are as follows:
[0059] The method for pore distribution testing of the present invention comprises the following steps: using a BELSORP-mini device to perform a nitrogen adsorption-desorption experiment at 77K, analyzing the adsorption-desorption curve by a Brunauer-Emmet-Teller (BET) method, calculating the specific surface area of the sample, and analyzing the desorption curve by a Barrett-Joyner-Halenda (BJH) method to obtain a pore size distribution curve of the material.
[0060] The method for testing the Young's modulus of the present invention comprises the following steps: after selecting a material sample, an atomic force microscope (AFM) is used to measure the Young's modulus; specifically, an RTESP-525 AFM (produced by Bruker) equipped with a silicon probe is used, and the test data is analyzed with the help of the Derjaguin-Muller-Toporov (DMT) model in the NanoScopeAnalysis software.
[0061] Example 1
[0062] This embodiment provides a metal-doped three-dimensional covalent organic framework material, and the preparation method thereof comprises the following steps:
[0063] 121.9365 mg (0.15 mmol) of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin cerium and 34.482 mg (0.1 mmol) of 9,10-[1,2]benzanthracene-2,3,6,7,14,15(9H,10H)-hexanone were weighed and mixed in 4 mL of n-butanol, and then 0.4 mL of 6 mol / L glacial acetic acid was added dropwise. The mixture was ultrasonically treated for 10 min, vacuum-cycled degassing was performed, and Schiff base polymerization was performed at 120°C for 72 h. After the reaction was completed, the mixture was filtered, and the residue was washed with acetone and tetrahydrofuran, and then vacuum-dried to obtain a metal-doped three-dimensional covalent organic framework material. The basic structure of the material can be found in Figure 1 , wherein the metal M in this embodiment is cerium.
[0064] The transmission electron microscope (TEM) image of the metal-doped three-dimensional covalent organic framework material prepared in this embodiment is as follows: Figure 2 As shown. Figure 2 It can be seen that metal-doped three-dimensional covalent organic framework materials are sheet-like structures.
[0065] The nitrogen adsorption-desorption curve of the metal-doped three-dimensional covalent organic framework material prepared in this embodiment is as follows: Figure 3 As shown, the pore size distribution diagram of the metal-doped three-dimensional covalent organic framework material prepared in this embodiment is as shown in Figure 4 The results show that the metal-doped three-dimensional covalent organic framework material in Example 1 has a large specific surface area, with a pore size range of 0-12 nanometers, concentrated in the range of 2-4 nanometers. The porous structure helps to accelerate ion transport and provides a solid foundation for improving the electrochemical performance of the material.
[0066] After measuring the Young's modulus of the metal-doped three-dimensional covalent organic framework material prepared in this embodiment, the results show that the surface Young's modulus of the metal-doped three-dimensional covalent organic framework material reaches 17GPa, and the Young's modulus of the two-dimensional covalent organic framework (2DCOF) ranges from 4 to 24GPa. The value of 17GPa is a relatively high level in the covalent organic framework (COF) material, and it has significant mechanical performance advantages even compared with traditional engineering materials, and has excellent mechanical strength. This high-strength characteristic is crucial for inhibiting the dendrite growth of lithium metal negative electrodes during charging and discharging, because good mechanical properties help to disperse stress concentration, thereby reducing the formation and growth of dendrites. Specifically, in battery applications, this high Young's modulus helps to improve the safety and stability of the battery, especially when operating at high current density, it can effectively prevent the occurrence of problems such as battery short circuit and thermal runaway. Therefore, the high Young's modulus of the COF material is a significant advantage as a battery negative electrode material.
[0067] This embodiment also provides a composite negative electrode for a metal secondary battery, and the preparation method thereof comprises the following steps:
[0068] 10 mg of the aforementioned metal-doped three-dimensional covalent organic framework material was uniformly dispersed in 10 ml of N-methylpyrrolidone to form a uniform mixed solution. In a glove box filled with argon (where the concentration of water and oxygen was less than 0.01 ppm), 30 μL of the solution was dripped onto a lithium metal sheet with a diameter of 15 mm. Subsequently, the lithium metal sheet dripped with the solution was placed on a heating table at 60°C and heated for 6 hours to evaporate the solvent. After the solvent was completely evaporated and cooled to ambient temperature, a composite negative electrode for a metal secondary battery was obtained.
[0069] This embodiment also provides a Li||Li symmetrical battery, and its preparation method includes the following steps: using the composite negative electrode for metal secondary batteries as a counter electrode and a lithium metal sheet as a working electrode to assemble a Li||Li symmetrical battery of model CR2032. The separator used in the battery is a Celgard2400 polypropylene microporous membrane, and the electrolyte is 1 mol / L LiTFSI / DOL+DME (V / V=1:1).
[0070] This embodiment also provides a lithium iron phosphate metal secondary battery, the preparation method of which includes the following steps:
[0071] According to the mass ratio of 8:1:1, lithium iron phosphate, superconducting carbon black (SuperP) conductive agent and polyvinylidene fluoride (PVDF) binder were weighed and mixed, and then N-methylpyrrolidone (NMP) with a mass of 19 times that of PVDF was added, and fully stirred into a paste, and coated on the current collector aluminum foil with a scraper, and then placed in a 60°C vacuum drying oven for 8h, and cut to prepare a pole piece (φ=15mm), and a pole piece with an active material load of 4mg was obtained as a metal secondary battery positive electrode. Then the metal secondary battery positive electrode and the above-mentioned composite negative electrode for metal secondary batteries were transferred to a glove box filled with argon gas for assembly of button batteries. The button battery model is CR2032, the diaphragm is a polypropylene microporous membrane Celgard2400, and the electrolyte is 1mol / L LiPF6 / EC+DMC+EMC (V:V:V=1:1:1).
[0072] Example 2
[0073] This embodiment provides a metal-doped three-dimensional covalent organic framework material, and the preparation method thereof comprises the following steps:
[0074] 129.752 mg (0.15 mmol) of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin iridium and 34.482 mg (0.1 mmol) of 9,10-[1,2]benzanthracene-2,3,6,7,14,15(9H,10H)-hexanone were weighed and mixed in 4 mL of n-butanol, and then 0.4 mL of 6 mol / L glacial acetic acid was added dropwise. The mixture was ultrasonically treated for 10 min, vacuum-cycled degassing was performed, and Schiff base polymerization was performed at 120°C for 72 h. After the reaction was completed, the mixture was filtered, and the residue was washed with acetone and tetrahydrofuran, and then vacuum-dried to obtain a metal-doped three-dimensional covalent organic framework material. The basic structure of the material can be found in Figure 1 , wherein the metal M in this embodiment is iridium.
[0075] This embodiment also provides a composite negative electrode for a metal secondary battery. The difference from Example 1 is that the metal-doped three-dimensional covalent organic framework material adopts the metal-doped three-dimensional covalent organic framework material of this embodiment, and its preparation method is the same as that of Example 1, so it is not repeated here.
[0076] This embodiment also provides a Li||Li symmetrical battery, which is different from Embodiment 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this embodiment, and its preparation method is the same as that in Embodiment 1, so it will not be described in detail.
[0077] This embodiment also provides a lithium iron phosphate metal secondary battery, which is different from Embodiment 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this embodiment, and its preparation method is the same as that in Embodiment 1, so it will not be described in detail.
[0078] Example 3
[0079] This embodiment provides a metal-doped three-dimensional covalent organic framework material, and the preparation method thereof comprises the following steps:
[0080] 130.181 mg (0.15 mmol) of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin platinum and 34.482 mg (0.1 mmol) of 9,10-[1,2]benzanthracene-2,3,6,7,14,15(9H,10H)-hexanone were weighed and mixed in 4 mL of n-butanol, and then 0.4 mL of 6 mol / L glacial acetic acid was added dropwise. The mixture was ultrasonically treated for 10 min, vacuum-cycled degassing was performed, and Schiff base polymerization was performed at 120°C for 72 h. After the reaction was completed, the mixture was filtered, and the residue was washed with acetone and tetrahydrofuran, and then vacuum-dried to obtain a metal-doped three-dimensional covalent organic framework material. The basic structure of the material can be found in Figure 1 , wherein the metal M in this embodiment is platinum.
[0081] This embodiment also provides a composite negative electrode for a metal secondary battery. The difference from Example 1 is that the metal-doped three-dimensional covalent organic framework material adopts the metal-doped three-dimensional covalent organic framework material of this embodiment, and its preparation method is the same as that of Example 1, so it is not repeated here.
[0082] This embodiment also provides a Li||Li symmetrical battery, which is different from Embodiment 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this embodiment, and its preparation method is the same as that in Embodiment 1, so it will not be described in detail.
[0083] This embodiment also provides a lithium iron phosphate metal secondary battery, which is different from Embodiment 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this embodiment, and its preparation method is the same as that in Embodiment 1, so it will not be described in detail.
[0084] Example 4
[0085] This embodiment provides a metal-doped three-dimensional covalent organic framework material, and the preparation method thereof comprises the following steps:
[0086] 130.464 mg (0.15 mmol) of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin gold and 34.482 mg (0.1 mmol) of 9,10-[1,2]benzanthracene-2,3,6,7,14,15(9H,10H)-hexanone were weighed and mixed in 4 mL of n-butanol, and then 0.4 mL of 6 mol / L glacial acetic acid was added dropwise. The mixture was ultrasonically treated for 10 min, vacuum-cycled degassing was performed, and Schiff base polymerization was performed at 120°C for 72 h. After the reaction was completed, the mixture was filtered, and the residue was washed with acetone and tetrahydrofuran, and then vacuum-dried to obtain a metal-doped three-dimensional covalent organic framework material. The basic structure of the material can be found in Figure 1 , wherein the metal M in this embodiment is gold.
[0087] This embodiment also provides a composite negative electrode for a metal secondary battery. The difference from Example 1 is that the metal-doped three-dimensional covalent organic framework material adopts the metal-doped three-dimensional covalent organic framework material of this embodiment, and its preparation method is the same as that of Example 1, so it is not repeated here.
[0088] This embodiment also provides a Li||Li symmetrical battery, which is different from Embodiment 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this embodiment, and its preparation method is the same as that in Embodiment 1, so it will not be described in detail.
[0089] This embodiment also provides a lithium iron phosphate metal secondary battery, which is different from Embodiment 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this embodiment, and its preparation method is the same as that in Embodiment 1, so it will not be described in detail.
[0090] Comparative Example 1
[0091] This comparative example provides a lithium metal sheet negative electrode for use in a metal secondary battery.
[0092] This comparative example also provides a Li||Li symmetrical battery, which differs from Example 1 in that the lithium metal sheet negative electrode of this comparative example is used instead of the composite negative electrode for the metal secondary battery described in Example 1. The preparation method is the same as that of Example 1, so it is not repeated here.
[0093] This comparative example also provides a lithium iron phosphate metal secondary battery, which is different from Example 1 in that the composite negative electrode for the metal secondary battery adopts the lithium metal sheet negative electrode of this comparative example, and its preparation method is the same as that of Example 1, so it is not repeated here.
[0094] Comparative Example 2
[0095] This comparative example provides a three-dimensional covalent organic framework material, and its preparation method comprises the following steps:
[0096] 101.219 mg (0.15 mmol) of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin and 34.482 mg (0.1 mmol) of 9,10-[1,2]benzanthracene-2,3,6,7,14,15(9H,10H)-hexanone were weighed and mixed in 4 mL of n-butanol, and then 0.4 mL of 6 mol / L glacial acetic acid was added dropwise. The mixture was ultrasonically treated for 10 min, vacuum-cycled for degassing, and heated at 120 °C for 72 h for Schiff base polymerization. After the reaction was completed, the mixture was filtered, and the residue was washed with acetone and tetrahydrofuran, and then vacuum-dried to obtain a three-dimensional covalent organic framework material. The basic structure of the material can be found in Figure 1 , the difference is that the metal M is not doped.
[0097] This comparative example also provides a composite negative electrode for a metal secondary battery. The difference from Example 1 is that the metal-doped three-dimensional covalent organic framework material adopts the three-dimensional covalent organic framework material of this comparative example, and its preparation method is the same as that of Example 1, so it is not repeated here.
[0098] This comparative example also provides a Li||Li symmetrical battery, which is different from Example 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this comparative example, and its preparation method is the same as that in Example 1, so it is not repeated here.
[0099] This comparative example also provides a lithium iron phosphate metal secondary battery, which is different from Example 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this comparative example, and its preparation method is the same as that in Example 1, so it is not repeated here.
[0100] Comparative Example 3
[0101] This comparative example provides a metal-doped three-dimensional covalent organic framework material, and the preparation method thereof comprises the following steps:
[0102] 109.7235 mg (0.15 mmol) of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin nickel and 34.482 mg (0.1 mmol) of 9,10-[1,2]benzanthracene-2,3,6,7,14,15(9H,10H)-hexanone were weighed and mixed in 4 mL of n-butanol, and then 0.4 mL of 6 mol / L glacial acetic acid was added dropwise. The mixture was ultrasonically treated for 10 min, vacuum-cycled degassing was performed, and Schiff base polymerization was performed at 120°C for 72 h. After the reaction was completed, the mixture was filtered, and the residue was washed with acetone and tetrahydrofuran, and then vacuum-dried to obtain a metal-doped three-dimensional covalent organic framework material. The basic structure of the material can be found in Figure 1 , the difference is that the metal M in this comparative example is nickel.
[0103] This comparative example also provides a composite negative electrode for a metal secondary battery. The difference from Example 1 is that the metal-doped three-dimensional covalent organic framework material adopts the metal-doped three-dimensional covalent organic framework material of this comparative example, and its preparation method is the same as that of Example 1, so it is not repeated here.
[0104] This comparative example also provides a Li||Li symmetrical battery, which is different from Example 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this comparative example, and its preparation method is the same as that in Example 1, so it is not repeated here.
[0105] This comparative example also provides a lithium iron phosphate metal secondary battery, which is different from Example 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this comparative example, and its preparation method is the same as that in Example 1, so it is not repeated here.
[0106] Comparative Example 4
[0107] This comparative example provides a three-dimensional covalent organic framework material, and its preparation method comprises the following steps:
[0108] 101.219 mg (0.15 mmol) of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin and 87.989 mg (0.1 mmol) of 4,4',4",4"',4"",4""'-(9,10-dihydro-9,10-[1,2]benzanthracene-2,3,6,7,14,15-hexayl)hexabenzaldehyde were weighed and mixed in 4 mL of n-butanol, and then 0.4 mL of 6 mol / L glacial acetic acid was added dropwise. The mixture was ultrasonically treated for 10 min, vacuum-cycled degassing was performed, and Schiff base polymerization was performed at 120°C for 72 h. After the reaction was completed, the mixture was filtered, and the residue was washed with acetone and tetrahydrofuran, and then vacuum-dried to obtain a three-dimensional covalent organic framework material. The basic structure of the material can be found in Figure 5 , the difference is that the metal M is not doped in this comparative example.
[0109] This comparative example also provides a composite negative electrode for a metal secondary battery. The difference from Example 1 is that the metal-doped three-dimensional covalent organic framework material adopts the three-dimensional covalent organic framework material of this comparative example, and its preparation method is the same as that of Example 1, so it is not repeated here.
[0110] This comparative example also provides a Li||Li symmetrical battery, which is different from Example 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this comparative example, and its preparation method is the same as that in Example 1, so it is not repeated here.
[0111] This comparative example also provides a lithium iron phosphate metal secondary battery, which is different from Example 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this comparative example, and its preparation method is the same as that in Example 1, so it is not repeated here.
[0112] Comparative Example 5
[0113] This comparative example provides a metal-doped three-dimensional covalent organic framework material, and the preparation method thereof comprises the following steps:
[0114] 121.9365 mg (0.15 mmol) of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin cerium and 87.989 mg (0.1 mmol) of 4,4',4",4"',4"",4""'-(9,10-dihydro-9,10-[1,2]benzanthracene-2,3,6,7,14,15-hexayl)hexabenzaldehyde were weighed and mixed in 4 mL of n-butanol, and then 0.4 mL of 6 mol / L glacial acetic acid was added dropwise. The mixture was ultrasonically treated for 10 min, vacuum-cycled degassing was performed, and Schiff base polymerization was carried out at 120°C for 72 h. After the reaction was completed, the mixture was filtered, and the residue was washed with acetone and tetrahydrofuran, and then vacuum-dried to obtain a metal-doped three-dimensional covalent organic framework material. The basic structure of the material can be found in Figure 5 , wherein the metal M in this comparative example is cerium.
[0115] This comparative example also provides a composite negative electrode for a metal secondary battery. The difference from Example 1 is that the metal-doped three-dimensional covalent organic framework material adopts the metal-doped three-dimensional covalent organic framework material of this comparative example, and its preparation method is the same as that of Example 1, so it is not repeated here.
[0116] This comparative example also provides a Li||Li symmetrical battery, which is different from Example 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this comparative example, and its preparation method is the same as that in Example 1, so it is not repeated here.
[0117] This comparative example also provides a lithium iron phosphate metal secondary battery, which is different from Example 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this comparative example, and its preparation method is the same as that in Example 1, so it is not repeated here.
[0118] Comparative Example 6
[0119] This comparative example provides a metal-doped three-dimensional covalent organic framework material, and the preparation method thereof comprises the following steps:
[0120] 129.752 mg (0.15 mmol) of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin iridium and 87.989 mg (0.1 mmol) of 4,4',4",4"',4"",4""'-(9,10-dihydro-9,10-[1,2]benzanthracene-2,3,6,7,14,15-hexayl)hexabenzaldehyde were weighed and mixed in 4 mL of n-butanol, and then 0.4 mL of 6 mol / L glacial acetic acid was added dropwise. The mixture was ultrasonically treated for 10 min, vacuum-cycled degassing was performed, and Schiff base polymerization was performed at 120°C for 72 h. After the reaction was completed, the mixture was filtered, and the residue was washed with acetone and tetrahydrofuran, and then vacuum-dried to obtain a metal-doped three-dimensional covalent organic framework material. The basic structure of the material can be found in Figure 5 , wherein the metal M in this comparative example is iridium.
[0121] This comparative example also provides a composite negative electrode for a metal secondary battery. The difference from Example 1 is that the metal-doped three-dimensional covalent organic framework material adopts the metal-doped three-dimensional covalent organic framework material of this comparative example, and its preparation method is the same as that of Example 1, so it is not repeated here.
[0122] This comparative example also provides a Li||Li symmetrical battery, which is different from Example 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this comparative example, and its preparation method is the same as that in Example 1, so it is not repeated here.
[0123] This comparative example also provides a lithium iron phosphate metal secondary battery, which is different from Example 1 in that the composite negative electrode for the metal secondary battery adopts the composite negative electrode prepared in this comparative example, and its preparation method is the same as that in Example 1, so it is not repeated here.
[0124] The Li||Li symmetrical batteries of Examples 1 to 4 and Comparative Examples 1 to 6 were subjected to electrochemical performance tests on a Xinwei test system under the test conditions of 1 mA / cm2 and 1 mAh / cm2. The test results are shown in Table 1 below.
[0125] Table 1
[0126]
[0127]
[0128] Table 1 shows that the Li||Li symmetric battery assembled in the embodiment of the present invention has lower nucleation overpotential, polarization voltage and longer cycle life than the Li||Li symmetric battery assembled in the comparative example.
[0129] The lithium iron phosphate metal secondary batteries of Examples 1 to 4 and Comparative Examples 1 to 6 were subjected to electrochemical performance tests on a Xinwei test system, with the test voltage range being 2.4-4.2 V. The test results are shown in Table 2 below:
[0130] Table 2
[0131]
[0132] Table 2 shows that the lithium iron phosphate metal secondary battery prepared by the method of the present invention has achieved significant improvement in the first discharge capacity and cycle retention rate compared with the battery assembled by the traditional method. This result confirms the effectiveness of the present invention in improving battery performance.
[0133] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.
Claims
1. A metal-doped three-dimensional covalent organic framework material, characterized in that: The metal-doped three-dimensional covalent organic framework material is formed by connecting a 9,10-dihydro-9,10-[1,2]benzanthracene skeleton and a metal-doped β-tetra-R-based porphyrin skeleton through nitrogen atoms. The 9,10-dihydro-9,10-[1,2]benzanthracene skeleton includes two first-dimensional connection sites, two second-dimensional connection sites and two third-dimensional connection sites. For any of the 9,10-dihydro-9,10-[1,2]benzanthracene skeletons, at least one of the first-dimensional connection sites is connected to the nitrogen atom through a double bond, at least one of the second-dimensional connection sites is connected to the nitrogen atom through a double bond, and at least one of the third-dimensional connection sites is connected to the nitrogen atom through a double bond. The four R groups of the metal-doped β-tetra-R-based porphyrin skeleton are respectively connected to one of the nitrogen atoms through a single bond. The metal includes one of cerium, iridium, platinum and gold.
2. The metal-doped three-dimensional covalent organic framework material according to claim 1, characterized in that: The structural formula of the metal-doped three-dimensional covalent organic framework material is: Wherein, M is one of cerium, iridium, platinum and gold.
3. A method for preparing a metal-doped three-dimensional covalent organic framework material according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: uniformly mixing metal-doped 5,10,15,20-tetrakis(4-aminophenyl)porphyrin with a three-dimensional keto compound, a glacial acetic acid solution and a first solvent, degassing, reacting at 100-150° C. for 72-120 hours, filtering, washing and drying to obtain the metal-doped three-dimensional covalent organic framework material; The metal is one of cerium, iridium, platinum and gold; the three-dimensional keto compound is formed by connecting the 9,10-dihydro-9,10-[1,2]benzanthracene skeleton and at least three oxygen atoms through double bonds, wherein at least one of the first-dimensional connection sites is connected to the oxygen atom, at least one of the second-dimensional connection sites is connected to the oxygen atom, and at least one of the third-dimensional connection sites is connected to the oxygen atom; the first solvent includes one or more of methanol, pyridine, N-methylpyrrolidone, o-dichlorobenzene, n-butanol, mesitylene and 1,4-dioxane.
4. The method for preparing a metal-doped three-dimensional covalent organic framework material according to claim 3, characterized in that: The three-dimensional keto compound is 9,10-[1,2]benzanthracene-2,3,6,7,14,15(9H,10H)-hexanone.
5. The method for preparing a metal-doped three-dimensional covalent organic framework material according to claim 3, characterized in that: The molar ratio of the keto carbonyl group in the three-dimensional keto compound to the amino group in the metal-doped 5,10,15,20-tetrakis(4-aminophenyl)porphyrin is 1:(1-1.2).
6. The metal-doped three-dimensional covalent organic framework material according to claim 1, characterized in that: The sum of the masses of the three-dimensional keto compound and the metal-doped 5,10,15,20-tetrakis(4-aminophenyl)porphyrin: the volume of the first solvent = 20 mg:(1-2) ml, the volume ratio of the first solvent to the glacial acetic acid solution is 1:(0.1-0.2), and the concentration of the glacial acetic acid solution is 6-12 mol / L.
7. A negative electrode, characterized in that The invention comprises an active metal and the metal-doped three-dimensional covalent organic framework material according to any one of claims 1 to 2, wherein the active metal comprises one or more of lithium, sodium, potassium and zinc.
8. The negative electrode according to claim 7, characterized in that The preparation method of the negative electrode comprises the following steps: uniformly dispersing the metal-doped three-dimensional covalent organic framework material in a second solvent to obtain a mixed solution, uniformly drop-coating the mixed solution on the surface of the active metal, and heating the active metal until the second solvent on the surface of the active metal is completely volatilized to obtain the negative electrode; The mass of the metal-doped three-dimensional covalent organic framework material: the volume of the second solvent = 1 mg: (1-3) mL; The amount of the mixed solution dripped on the active metal surface is 0.17-0.28 μL / mm 2 .
9. The negative electrode according to claim 8, characterized in that The method for preparing the negative electrode further comprises the following steps: heating the active metal to a temperature of 40-80° C. and heating the active metal for a time of 4-12 hours.
10. A secondary battery, characterized in that: The invention comprises a battery shell and the negative electrode according to any one of claims 7 to 9, a lithium iron phosphate positive electrode, a separator and an electrolyte located in the battery shell, wherein the separator is located between the positive electrode and the negative electrode.
Citation Information
Patent Citations
Three-dimensional metalloporphyrin-based covalent organic framework material with stp topological network structure and preparation method and application thereof
CN113881004A
Silicone polyurethane copolymers containing oxygen sensitive phosphorescent dye compounds
US5155149A